Changing gull diet in a changing world: A 150‐year stable isotope (δ13C, δ15N) record from feathers collected in the Pacific Northwest of North America. (5th December 2014) - Blight, Louise K.; Hobson, Keith A.; Kyser, T. Kurt; Arcese, Peter
Abstract The world's oceans have undergone significant ecological changes following European colonial expansion and associated industrialization. Seabirds are useful indicators of marine food web structure and can be used to track multidecadal environmental change, potentially reflecting long‐term human impacts. We used stable isotope (δ13C, δ15N) analysis of feathers from glaucous‐winged gulls (Larus glaucescens) in a heavily disturbed region of the northeast Pacific to ask whether diets of this generalist forager changed in response to shifts in food availability over 150 years, and whether any detected change might explain long‐term trends in gull abundance. Sampled feathers came from birds collected between 1860 and 2009 at nesting colonies in the Salish Sea, a transboundary marine system adjacent to Washington, USA and British Columbia, Canada. To determine whether temporal trends in stable isotope ratios might simply reflect changes to baseline environmental values, we also analysed muscle tissue from forage fishes collected in the same region over a multidecadal timeframe. Values of δ13C and δ15N declined since 1860 in both subadult and adult gulls (δ13C, 2–6‰; δ15N, 4–5‰), indicating that their diet has become less marine over time, and that birds now feed at a lower trophic level than previously. Conversely, forage fish δ13C and δ15N values showed no trends, supporting our conclusion that gull feather values were indicative of declines in marine food availability rather than of baseline environmental change. Gradual declines in feather isotope values are consistent with trends predicted had gulls consumed less fish over time, but were equivocal with respect to whether gulls had switched to a more garbage‐based diet, or one comprising marine invertebrates. Nevertheless, our results suggest a long‐term decrease in diet quality linked to declining fish abundance or other anthropogenic influences, and may help to explain regional population declines in this species and other piscivores.